Pews, prayers, and participation : religion and civic responsibility in America - Smidt, Corwin E., 1946- (Religion and politics series (Georgetown University), 2008)
Is the "private" experience of religion counterproductive to engagement in public life? Does the "public" experience of religion contribute anything distinctive to civic engagement? Pews, Prayers, and Participation offers a fresh approach to key questions about what role religion plays in fostering civic responsibility in contemporary American society. Written by five prominent scholars of religion and politics, led by Calvin College's Corwin Smidt, the book brilliantly articulates how religion shapes participation in a range of civic activities--from behaviors (such as membership in voluntary associations, volunteering, and charitable contributions) to capacities (such as civic skills and knowledge), to virtues (such as law-abidingness, tolerance, and work ethic). In the course of their study the authors examine whether an individual exhibits a diminished, a privatized, a public, or an integrated form of religious expression, based on the individual's level of participation in both the public (worship) or private (prayer) dimensions of religious life. They question whether the privatization of religious life is counterproductive to engagement in public life, and they show that religion does indeed play a significant role in fostering civic responsibility across each of its particular facets. Pews, Prayers, and Participation is a bold and provocative clarion call to the continuing importance and changing nature of religion in American public life. It will be of particular interest to students and scholars of religion and politics, and culture and politics, as well as general readers with an interest in the impact of religion in the public sphere."--Google Books viewed Mar. 11, 2021